Simultaneous determination of eight biologically active thiol compounds using gradient elution-liquid chromatography with Coul-Array detection - Petrlova, Jitka; Mikelova, Radka; Stejskal, Karel; Kleckerova, Andrea; Zitka, Ondrej; Petrek, Jiri; Havel, Ladislav; Zehnalek, Josef; Vojtech, Adam; Trnkova, Libuse; Kizek, Rene (Journal of separation science, 2006)
The most active form of sulfur in biomolecules is the thiol group, present in a number of biologically active compounds. Here we present a comprehensive study of thiol analysis using flow injection analysis/HPLC with electrochemical detection. The effect of different potentials of working electrodes, of organic solvent contents in the mobile phase, and of isocratic and gradient elution on simultaneous determination of thiol compounds (cysteine, cystine, N-acetylcysteine, homocysteine, reduced and oxidised glutathione, desglycinephytochelatin, and phytochelatins) are described and discussed. These thiol compounds were well separated and detected under optimised HPLC-electrochemical detection conditions (mobile phase: 80 mM trifluoroacetic acid and methanol with a gradient profile starting at 97:3 (TFA:methanol), kept constant for the first 8 min, then decreasing to 85:15 during one minute, kept constant for 8 min, and finally increasing linearly up to 97:3 from 17 to 18 min; the flow rate was 0.8 mL/min, column and detector temperature 25 degrees C, and the electrode potential 900 mV). We were able to determine tens of femtomoles (3 S/N) of the thiols per injection (5 microL), except for phytochelatin5 whose detection limit was 2.1 pmole. This technique was consequently used for simultaneous determination of compounds of interest in biological samples (maize tissue and human blood serum).
Keywords: senzitivita a specificita; rozpouštědla; molekulární struktura; kukuřice setá; Reproducibility of Results; Molecular Structure; Zea mays; Chromatography, Liquid; sulfhydrylové sloučeniny; Serum; sérum; lidé; Sulfhydryl Compounds; Humans; Solvents; reprodukovatelnost výsledků; chromatografie kapalinová; Sensitivity and Specificity